Beneficial effects of AOS-iron supplementation on intestinal structure and microbiota in IDA rats - Hong He; Hui Teng; Qun Huang; Dan He; Fengping An; Lei Chen; Hongbo Song (Food Science and Human Wellness)
The objective of this study was to investigate the effects of agar oligosaccharide-iron (AOS-iron) on intestinal tissue pathology and microbiota in IDA rats induced by a low-iron diet, further to find the relationship between intestinal microbiota and iron metabolic disorders. After 4 weeks of AOS-iron supplementation, the fecal iron content of IDA rats markedly increased in a dose-dependent manner, only the damaged cecum and colon tissues in medium-dose (MD) and high-dose (HD) groups were repaired to the baseline, while the diversity of gut microbiota was improved even at low dose (LD). Furthermore, the supplementation of AOS-iron altered the composition of gut microbiota. At the genus level, the beneficial microbiota was enriched in AOS-iron groups, but the relative abundance of potential opportunistic pathogens obviously reduced compared to that in the anemia model (AM) group. Spearman’s correlation analysis revealed that biochemical parameters, including blood metabolic parameters, iron contents, body weight, GSH-PX and T-AOC activity, were positively correlated with SMB53, Anaerotruncus, Anaerostipes and Coprobacillus but negatively correlated with Morganella, Fusobacterium and Serratia. These findings indicated that AOS-iron effectively repaired the damaged intestinal tissue and ameliorated iron metabolic disorders by regulating gut microbiota desirably, which could provide references for the treatment of IDA.